Wearable triboelectric nanogenerator using a plasma-etched PDMS–CNT composite for a physical activity sensor - Kim, Min-Ki; Kim, Myoung-Soo; Kwon, Hong-Bum; Jo, Sung-Eun; Kim, Yong-Jun (RSC advances, 2017)
Triboelectric nanogenerators (TENGs) have recently shown promising potential as effective energy harvesters using human motion energy. However, the efficiency of polymer-based flexible TENG must be enhanced for various applications. In this work, we propose a flexible TENG with a fluorocarbon plasma-etched polydimethylsiloxane (PDMS)–carbon nanotube (CNT). The fluorocarbon plasma etching causes not only a chemical modification, but also a physical effect on the morphology of the PDMS–CNT surface to enhance the TENG output performance. The added CNT enhances the mechanical properties, such as durability, of a thin film. The etched PDMS structure and the revealed CNTs increase the charge density on the surface. We confirm the effect of different CNT concentrations doped in PDMS and various etching times. We propose a TENG with 4 wt% CNT, which has been subjected to fluorocarbon etching for 60 s. The TENG exhibits an output voltage of 77.8 V, which is 248.7% and 106.5% higher than that of pure PDMS and un-etched PDMS–CNT, respectively. The 20 mm × 30 mm TENG delivers an output power of 1.98 mW (3.29 W m −2 ) at a matching resistance of 3 MΩ. The TENG exhibits good stability and superior electrical performance, making it capable of driving both the instantaneous operation of 70 LEDs and the charging of a 0.33 μF capacitor to 6.6 V. Furthermore, this TENG can be used as a self-powered physical activity sensor that measures the amount of human activity through the amount of charge in the capacitor.